Dose–response relationship between local anesthetic volume and hemidiaphragmatic paresis following ultrasound-guided supraclavicular brachial plexus blockade. Issue 12 (1st October 2020) - Tedore, Tiffany R; Lin, Hannah X; Pryor, Kane O; Tangel, Virginia E; Pak, Daniel J; Akerman, Michael; Wellman, David S; Oden-Brunson, Hannah
Abstract : Background: There is no consensus regarding what volume of local anesthetic should be used to achieve successful supraclavicular block while minimizing hemidiaphragmatic paresis (HDP). This study investigated the dose–response relationship between local anesthetic volume and HDP after ultrasound-guided supraclavicular brachial plexus block. Methods: A dose escalation design was used to define the dose response curve for local anesthetic volume and incidence of HDP in subjects undergoing upper extremity surgery with supraclavicular block as the primary anesthetic. Dosing levels of 5, 10, 15, 20, 25, 30, 35 and 40 mL of local anesthetic were administered in cohorts of three subjects per dose. Diaphragm function was assessed with M-mode ultrasound before and after block. Secondary objectives included assessment of negative inspiratory force (NIF), oxygen saturation, subjective dyspnea and extent of sensory and motor blockade. Results: Twenty-one subjects completed the study. HDP was present at all doses, with an incidence of 33% at 5 mL to 100% at 30–35 mL. There was a significant decrease in NIF (7.5 cmH2 O, IQR (22, 0); p=0.01) and oxygen saturation on room air (1%, IQR (2, 0); p=0.01) 30 min postblock in subjects experiencing HDP but not in those without HDP. There was no increase in dyspnea in subjects with or without HDP. No subject required respiratory intervention. Motor and sensory block improved with increasing dose, and subjects with HDP exhibited denser blocks than those without (p<0.01). Conclusions: There is no clinically relevant volume of local anesthetic at which HDP can be avoided when performing a supraclavicular block. In our subject population free of respiratory disease, HDP was well tolerated. Trial registration number: NCT03138577 .